Monsoon wedding - Nair, Mira; Baron, Caroline; Dhawan, Sabrina; Shah, Naseeruddin; Dubey, Lillete; Shetty, Shefali; Raaz, Vijay; Shome, Tillotama; Das, Vasundhara; Kharbanda, Kulbhusan (Universal, 2002)
Shot in New Delhi in 30 days, this film about a Punjabi wedding brings out all the frenzy and frolic, the loyalties, filial bonds and friendships, along with skeletons in the cupboard associated with such family events.